Mpox virus: virology, molecular epidemiology, and global public health challenges - Chen, Siwei; Huang, Ju; Chen, Junkai; Liu, Fengqi; Wang, Shuqi; Wang, Na; Li, Ming; Zhang, Ziyi; Huang, Congcong; Du, Weixing; Liu, Long; Liu, Zhixin (Frontiers in Microbiology, 2025)
Monkeypox (Mpox), a zoonotic disease caused by the Mpox virus (MPXV), has re-emerged as a significant global health concern, particularly since the 2022 outbreaks in non-endemic countries. MPXV shares close virological and genetic similarities with other orthopoxviruses, notably variola virus. The current circulating strains, primarily of clade IIb, exhibit enhanced human-to-human transmissibility. This review synthesizes recent advances in MPXV virology, pathogenesis, molecular evolution, clinical features, and diagnostic techniques. In addition, we highlight the mounting public health challenges, including vaccine inequity, immunity gaps in the post-smallpox era, surveillance limitations, healthcare system vulnerabilities, and stigma-related barriers to disease reporting and control. Addressing these multifaceted issues requires a globally coordinated response integrating equitable vaccine access, strengthened surveillance, stigma-free health education, and harmonized outbreak response strategies. A comprehensive understanding of these factors is critical to preventing future large-scale outbreaks and mitigating the global health burden posed by MPXV.